CHANGE IN SPATIAL AND TEMPORAL CHARACTERISTICS OF RAINFALL IN EAST JAVA PROVINCE IN RELATION TO GLOBAL CLIMATE CHANGE PERUBAHAN KARAKTERISTIK CURAH HUJAN MENURUT RUANG DAN WAKTU DI PROVINSI JAWA TIMUR DALAM KAITANNYA DENGAN PERUBAHAN IKLIM ... - Moh. Ismail Wahab; S. Sudibyakto; Sunarto Gunadi; W.S. Suratman (Agromet, 2009)
This study aims to analyze spatial and temporal variation of rainfall in the year 1971 until the year 2007 that is divided into two (2) periods ie 1971-1989 and 1990-2007 in relat ion to climate global change. The research was conducted in the area of East Java province from July until December 2008. The secondary data used in the research were: 1) Rainfall monthly data from 106 stations located in East Java within the period of 1971-2007 obtained from the Agency for Meteorology and Geophysical Karangploso Malang, 2) Sea Surface Temperature Nino 3.4 (http ://www.cpc.ncep.noaa.gov.), 3) Soil map scale 1: 250,000 obtanined from the Center Institute for Environmental Resource Management of Agriculture, and the map of Agroecological Zone (AEZ) of East Java scale 1: 250,000 from Assessment Institute for Agricultural Technology East Java. The analysis of rainfall characteristic consists of a) the changes of climate type Oldeman, b) the changes of the early dry and rainy season, c) the changes in of rainfall amount in dry and rainy season. The results showed that in 1971-1989 periods, the type of Oldeman climate in East Java vary from B1 to E, but after the 1990s the type of Oldeman climate change varied from C1 to D4 meaning that a part of East Java area (16.7%) become drier and 17.8% area of East Java became wet. The analysis of rainfall stations (106 stations) showed that some of rainfall stations (58.49%) have decreased the number of dry season rainfall about 3 - 500 mm/season. 56 stations (52.8%) have increased the number of rainy season rainfall in the range 1-600 mm /rainy season, while the 49 rainfall stations (46.22%) have decreased the number of rainfall in the range of 1-500 mm/season. Changes in the characteristics of rainfall in East Java, which occurred within the period of 1971-1989 and 1990-2007 was caused by the ENSO phenomenon.